Songs of the Silent Hearts: Spiritual Expressions of the Deaf and Mute Community of South Kalimantan's GERKATIN Community - Lantigimo, Enta Malasinta; Ripaldi, Ripaldi; Saputra, Perdana (TELEIOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
Abstract:This study explores the spiritual expressions of Deaf communities within GERKATIN South Kalimantan and examines how non-verbal forms of worship function as authentic manifestations of Christian and religious spirituality. The research aims to understand how Deaf individuals articulate their faith in the absence of auditory and verbal communication, and how their embodied, visual, and relational expressions form a meaningful spiritual experience. Using a qualitative research design, the study employs interviews, observations, and document analysis to investigate the lived experiences of Deaf individuals, focusing on their religious participation, social challenges, and alternative modes of expressing faith. The findings reveal that Deaf spirituality is shaped significantly by visual engagement, bodily expression, sign language, and communal relationships, all of which serve as powerful vehicles of meaning-making in their religious life. The study identifies a notable gap in public facilities, inclusive worship spaces, educational access, and pastoral support that continues to marginalise the Deaf community. The novelty of this research lies in its articulation of Deaf spirituality as a legitimate locus of theological reflection—demonstrating that silence, embodiment, and visuality are not deficiencies but rich spiritual resources. The implications of this study call for broader ecclesial and societal transformation, encouraging churches, religious leaders, and policymakers to adopt inclusive practices, integrate sign language and visual liturgy, and affirm Deaf individuals as full participants in spiritual and communal life.